Cubic Trigonometric B-spline Method for Solving a Linear System of Second Order Boundary Value Problems (European Journal of Pure and Applied Mathematics, 2023)
This paper introduces a novel trigonometric B-spline collocation method for solving a specific class of second-order boundary value problems. The study showcases the method’s practicality and effectiveness through various numerical examples. Furthermore, it evaluates the technique’s performance by calculating maximum errors for different step sizes in the spatial domain. The paper also conducts a comparative analysis with alternative methods, demonstrating the superior accuracy of the trigonometric B-spline approach.
Keywords: Linear system of second order boundary value problems; boundary value problems; cubic trigonometric B-spline basis functions